PENGGUNAAN MAPLE UNTUK MENINGKATKAN MOTIVASI BELAJAR DAN PRESTASI BELAJAR MATA KULIAH KALKULUS - Aziz Ahmadi; Eka Putra Wahyu Suminar (LPPM Press STKIP PGRI Pacitan, 2017)
This study is a class action research that aims to improve learning motivation and learning achievement of students in the subject of the calculus. The study was conducted in two cycles with the following results. Learning achievement results obtained in the first cycle that only 14 students or 17.07% that scored at least 70 of all students and obtained an average score of students learning motivation questionnaire is at high category that is at score 48 (scale 15-75). The results of the second cycle obtained an average score of students learning motivation questionnaire is 50, which means at the high category as well as an improvement in terms of learning achievement that there are 56 students or 68.29% that scored at least 70 of all students so that indicators of success has been achieved.